How Principals’ Instructional Leadership Influence Teachers’ Self-Efficacy - Tep, Sopheng; Loch, Ratana; Pok, Visalboth (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the Study: This study focuses on evaluating the degree of TEP of PIL on TSE in Cambodia. It also seeks to identify how TEP on PIL varies according to different demographic characteristics. Furthermore, the researcher aims to uncover whether teachers’ demographic characteristics influence their perception of instructional leadership from their principals. Methodology: The researcher employed descriptive statistics to measure TEP on PIL and used independent sample t-tests and one-way ANOVA to examine differences in TEP on PIL across various demographic characteristics. A total of 295 PJHSTs participated in this study, all of whom were pursuing higher education degrees at a private university in Phnom Penh. Main Findings: The results of the research indicate that PJHSTs have diverse perceptions of PIL. These positive perceptions suggest that PIL significantly influences TSE. Additionally, the findings revealed that teachers’ gender had a significant impact on their perceptions of PIL (p < 0.05). However, no significant impact of gender differences on TSE was found. The study also highlighted additional findings, as presented in the results section. Novelty/Originality of the Study: These findings provide valuable insights into fostering TSE through effective PIL in Cambodian school context. PIL emerges as a critical factor in enhancing TSE, as teachers with high self-efficacy tend to perform their teaching tasks more effectively. Consequently, school principals, academic staff, teachers, and other stakeholders can apply these findings to improve institutional success. Future research should explore other leadership styles and additional factors that may influence TSE.